27 Seven-year review of mitral valve repair rates and early outcomes for degenerative mitral disease. (October 2018) - Casey, L; Hayes, A; McCarthy, J
Abstract : Introduction and aims: Degenerative disease remains the most common underlying pathology of primary mitral regurgitation (MR) in our region. Guidelines for management of the condition advise that, when surgical management is indicated, mitral valve repair should be the first line approach. A seven-year review was conducted of mitral valve repair for degenerative MR performed by a single surgeon. We aim to determine repair rates and early results. Methods: The operative notes, discharge summaries and echo findings of all patients who underwent elective or scheduled mitral valve surgery from January 2011 until April 2018 were reviewed. Cases of degenerative disease were reviewed to compare actual versus predicted repair rates. Results: 238 patients underwent mitral valve surgery for severe degenerative MR, of whom 99% (n=235) were successfully repaired. A concomitant procedure was performed in 70% (n=166) of cases. Systolic anterior motion was noted on the immediate post-repair trans-oesophageal echocardiogram in 0.8% (n=2) of cases, necessitating re-establishment of cardiopulmonary bypass and re-repair. 100% (n=238) of patients had no MR, trivial MR, or MR of1 +on their post-operative echocardiography. The in-hospital mortality was 0.4% (n=1) in this population. The mortality occurred in an 85-year-old female patient due to CVA day 5-post op. Conclusion: Severe degenerative mitral regurgitation may be repaired with good outcomes for the vast majority of the population with the disease, when repair is performed in a specialist centre.